Mind mapping with problem-posing: Can it affect student’s problem-solving skills in Schoology-based learning? - Miswandi Tendrita; Muhammad Fath Azzajjad; Dewi Satria Ahmar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Problem-solving skills are essential to help students in expressing their ideas. However, problem posing is a method that can empower problem-solving skills. This study aims to determine the effectiveness of mind mapping assisted with a problem-posing method in online Schoology-based learning. This experimental research used the posttest-only control group. The subject of this study were students of the Department of Biology Education, 2020/2021 academic year, Universitas Sembilanbelas November Kolaka. The sample was divided into an experimental class and a control class. The research instrument was post-test questions that were made based on the indicators of problem-solving skills. The result showed that the experimental class has the highest score on each indicator of problem-solving skills. In addition, the hypothesis testing result with a significance p-value was 0.025 (<0.05). It can be concluded that there is a significant difference between the experimental class and the control class. The average value of problem-solving skills in the experimental class is also higher than in the control class. These results indicated that the mind mapping assisted with a problem-posing method in online Schoology-based learning is effective in improving students' problem-solving skills.